HYPOHIDROTIC ECTODERMAL DYSPLASIA - Bajpai, Manas; Pardhe, Nilesh (Journal of Ayub Medical College Abbottabad, 2015)
A 23 year old lady reported with the chief complain of missing teeth. She had been diagnosed much earlier by the physicians for Ectodermal dysplasia. General examination revealed sparse hair, absence of eyelashes and eyebrows with frontal bossing and averted lips. The skin was dry and wrinkled. She had numerous eczematous lesions in lower extremities. There was a history of reduced sweating and heat intolerance